Pendampingan Untuk Peningkatan Kapasitas Takmir Dalam Mengelola Keuangan Masjid (Tata Kelola Dana Umat yang Transparan, Akuntabel, dan Amanah) - Hasbullah Hajar; Muhammad Ridwan; Abubakar Esa; Rahyuni Rahayu; Sastia La Ijira (Universitas Negeri Surabaya, 2025)
To produce transparent and accountable mosque financial governance, capability is needed to prepare mosque financial reports. Currently, the best guide for preparing financial reports is ISAK 35 which is an IAI product. Many mosque takmirs, especially in Ternate, still face the issue of mosque financial management due to the lack of understanding regarding accountable and transparent financial reporting. On this basis, the PKM team took this issue as the main problem which will be resolved by carrying out capacity building assistance for mosque takmirs in financial management. From the training carried out, it was found that there was an increase in capability in preparing mosque financial reports for mosque takmirs who took part in training activities carried out by the PKM team. In this way, it is hoped that the mosque takmir can provide accountable and transparent accountability for the community funds he manages. The main implication is the increasing trust of organizations and individual people in entrusting funds to mosques in Ternate.